The Generation of Difluoroketenimine and Its Application in the Synthesis of α, α‐Difluoro‐β‐amino Amides. Issue 17 (22nd March 2019) - Zhang, Rui; Zhang, Zhikun; Zhou, Qi; Yu, Lefei; Wang, Jianbo
Abstract: Fluorine‐containing β‐amino acids and their derivatives have attracted significant attention due to their importance in life sciences. Herein the previously unknown difluoroketenimine, the analogue of the elusive difluoroketene, has been generated by the reaction of difluorocarbene and isocyanide, which further undergoes [2+2] cycloaddition with imine. The three‐component reaction affords α, α‐difluoro‐β‐amino amides in good yields. Mechanistic studies reveal the unique properties of the difluoroketenimine in the [2+2] cycloaddition with imine. Abstract : Difluoroketenimine, the analogue of the elusive difluoroketene, has been generated for the first time by the reaction of difluorocarbene and isocyanide, and further undergoes [2+2] cycloaddition with imine. The three‐component reaction affords α, α‐difluoro‐β‐amino amides in good yields. Mechanistic studies reveal the unique properties of the difluoroketenimine in the [2+2] cycloaddition with imine.